MARY LYNN RITZENTHALER, Preserving Archives and Manuscripts, 2nd ed. - Rekrut, Ala (Archivaria, 2011)
Preserving Archives and Manuscripts, 2nd ed. MARY LYNN RITZENTHALER. Chicago: Society of American Archivists, 2010. 544 p. ISBN 1-931666-32-6